The next generation of policy-driven language testing systems: accountability, consequences, and learning - Micheline Chalhoub-Deville (Language Testing in Asia)
Abstract High-stakes accountability testing systems play a central role in the global phenomenon of educational reform. While accountability testing tracks student performance, it also evaluates how well schools are helping students progress toward goals such as being college- or career-ready by high school graduation. Low-performing schools receive reduced funding or face closure. The premise is that student outcomes are shaped by the quality of instruction, resources, and support provided by schools and educators. Concerns persist, however, about whether these testing systems fairly reflect school performance or disproportionately punish schools with greater challenges without adequate support. This special issue of Language Testing in Asia is based on the joint symposium of the International Language Testing Association (ILTA) and the American Association of Applied Linguistics (AAAL). The scholarship presented in this issue addresses a critical gap in the field by examining the socio-educational context of accountability testing and the validation of aggregated scores. The authors in this issue investigate the alignment between reform-driven mandates and their testing systems in terms of learning, practices, and the impact on students, educators, and education. Contributors to this special issue call for socially grounded approaches to test validation and underscore the importance of both individual, group, and system-level considerations in validity research.